2016
DOI: 10.1007/s40195-016-0445-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Graphene–Titanium Composites Synthesized by Microwave Sintering

Abstract: The x wt% graphene-Ti composites (x = 0, 0.2, 0.3 and 0.4) were obtained using the powder metallurgy method. The X-ray diffraction results demonstrated that the peak intensity of graphene increased monotonically with increasing graphene content. Furthermore, the number of grain boundary and interface between graphene and matrix increased as graphene increased, which led to a sharp rise of thermal resistances. The thermal conductivity and specific heat capacity of composites initially decreased drastically with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Furthermore, thermodynamic analysis (∆G < 0) revealed that the reaction (Equation(7)) could be carried out when the temperature was higher than 720 °C [ 38 ]. Based on the result of the XRD ( Figure 4 ) and TEM ( Figure 8 ), Equations (8) and (9) are the chemical reactions in this study which have been inferred from literatures [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Additionally, Ti x P y detected by XRD ( Figure 4 ) was formed by the reaction between titanium and phosphorus which was derived from Equations (10) to (11).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, thermodynamic analysis (∆G < 0) revealed that the reaction (Equation(7)) could be carried out when the temperature was higher than 720 °C [ 38 ]. Based on the result of the XRD ( Figure 4 ) and TEM ( Figure 8 ), Equations (8) and (9) are the chemical reactions in this study which have been inferred from literatures [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Additionally, Ti x P y detected by XRD ( Figure 4 ) was formed by the reaction between titanium and phosphorus which was derived from Equations (10) to (11).…”
Section: Discussionmentioning
confidence: 81%
“…Xu et al found that although the lubricating property of MLG would disappear when the temperature was higher than 600 °C, the MLG had higheroxygen resistance due to the closed grain boundary, inhibiting the flow of oxygen from the grain boundary [ 25 ]. However, in general, the dispersion and integrity of graphene in composites still remain a problem to be solved [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that both CNTs-HA and graphene sheet-HA composites are ideal materials for bone tissue engineering scaffolds and beneficial to the proliferation and differentiation of human fetal osteoblastic cell line (hFOB 1.19) [ 23 ]. Yang et al found that compressive strength of graphene-Ti composites improve with the addition of an appropriate amount of graphene, which is also partly due to the enhancement effect of graphene itself [ 24 ]. However, the agglomeration of graphene occurred around some pores present on the surface of the composite [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al found that compressive strength of graphene-Ti composites improve with the addition of an appropriate amount of graphene, which is also partly due to the enhancement effect of graphene itself [ 24 ]. However, the agglomeration of graphene occurred around some pores present on the surface of the composite [ 24 ]. On the other hand, an appropriate amount of CNTs and GNFs have synergistic enhancement effects due to their unique structure [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCrAlY (M = Co or/and Ni) coatings prepared by thermal spraying technique have been diffusely used in the industries of nuclear power, aerospace and automotive owing to the excellent high-temperature corrosion and oxidation resistance and it could withstand the high thermal and mechanical loads due to possessing excellent high-temperature self-lubricating properties [1][2][3][4][5][6]. Graphite and molybdenum disulfide usually acted as solid lubricants could improve the tribological properties of the composites [7][8][9][10][11][12][13][14][15]. But this kind of solid lubricants would be oxidized or decomposed above 500°C, and therefore lose their lubricating effects [16].…”
Section: Introductionmentioning
confidence: 99%